The Relationship of Kidney Function, Cardiovascular Morbidity, and All-Cause Mortality: a Prospective Primary Care Cohort Study - Korhonen Päivi E.; Kiiski Sem; Kautiainen Hannu; Ojanen Seppo; Tertti Risto (Springer, 2025)
Background: Lower-than-normal estimated glomerular filtration rate (eGFR) is associated with the risk for all-cause mortality and adverse cardiovascular events. In this regard, the role of higher-than-normal eGFR is still controversial.
Objective: Investigate long-term clinical consequences across the levels of eGFR calculated by the creatinine-based Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation among apparently healthy cardiovascular risk subjects.
Design: Prospective study.
Participants: Participants (n=1747) of a population-based screening and intervention program for cardiovascular risk factors in Finland during the years 2005-2007.
Main measures: Cardiovascular morbidity and all-cause mortality.
Key results: Over the 14-year follow-up, subjects with eGFR ≥105 ml/min/1.73 m2 (n=97) had an increased risk for all-cause mortality [HR 2.15 (95% CI: 1.24-3.73)], incident peripheral artery disease [HR 2.62 (95% CI: 1.00-6.94)], and atrial fibrillation/flutter [HR 2.10 (95% CI: 1.21-3.65)] when compared to eGFR category 90-104 ml/min after adjustment for cardiovascular and lifestyle-related risk factors. The eGFR category ≥105 ml/min was also associated with a two-fold increased mortality rate compared to the Finnish general population.
Conclusions: Renal hyperfiltration defined as eGFR ≥105 ml/min/1.73 m2 is a frequent and important finding in patients commonly treated in primary care. These patients should be followed closely for timely interventions, such as strict BP and blood glucose regulation.